Awareness and knowledge of mothers of under five children regarding immunization in Ahmedabad - Rachna Kapoor; Sheetal Vya (Indian Association of Preventive and Social Medicine, 2010)
Research question: What is the level of knowledge of mothers of Under Five Children, attending the Immunization centre of Postpartum Unit , VS General Hospital, Ahmedabad regarding immunization? Objective: To assess the awareness & knowledge of mothers of Under Five children regarding Immunization. Study Design: Cross sectional descriptive study. Study Area/ Setting: Immunization centre of Post Partum Unit, VS General Hospital, Ahmedabad. Participants & Sample size : 100 mothers of Under Five children were studied from March 2009 to May 2009. Results: Mean age of the respondents was 28.4 years. 72% of the respondents were housewives & 65% of them were Hindus. 83% of the literate mothers had some knowledge about VPDs. 85% of the respondents knew about poliomyelitis & only 15% knew about Hepatitis B. 80% of respondents had no knowledge about Vitamin A. Main sources of information of mothers about VPD's was Anganwadi Worker 47% & Television 35%.